(untitled) (Research, Society and Development, 2020)
The Chikungunya virus has an African origin and is currently found in several parts of the world. In Brazil, the first reports occurred in mid-2010, and since then, there has been a considerable increase in infections, in view of the need for greater attention to this pathology. Objective: to carry out an integrative review on Chikungunya, including an article from the period 2014 to 2020, referring to data that covered Brazil, as well as to discuss how the process of spreading the disease and its particularities occurs, in addition to providing for clinical aspects, epidemiological, immunological. Methodology: an integrative review was carried out, where articles published on three platforms were selected as scientific databases: Science Direct, Pubmed and Scientific Electronic Library Online (SciELO), using the keywords Chikungunya and Brazil characterization, transmission, epidemiological aspects, clinical aspects, immunological aspects and treatment. Results: It is noticed that there is a correlation between the approaches used, reporting increased incidence, in addition to mentioning the vulnerabilities for the acquisition of such pathology. Conclusion: it is concluded that prevention should be a priority, especially with risk groups.